7Be in the outburst of the ONe nova V6595 Sgr. Issue 3 (26th November 2021) - Molaro, P; Izzo, L; D'Odorico, V; Aydi, E; Bonifacio, P; Cescutti, G; Harvey, E J; Hernanz, M; Selvelli, P; della Valle, M
ABSTRACT: We report on the search for the 7 Be ii isotope in the outbursts of the classical nova V6595 Sgr by means of high-resolution Ultraviolet and Visual Echelle Spectrograph (UVES) observations taken at the European Southern Observatory's Very Large Telescope in 2021 April, about two weeks after its discovery and under difficult circumstances due to the pandemic. Narrow absorption components with velocities at ∼ −2620 and −2820 km s −1, superposed on broader and shallow absorption, are observed in the outburst spectra for the 7 Be ii λλ313.0583, 313.1228 nm doublet resonance lines, as well as in several other elements such as Ca ii, Fe i, Mg i, Na i, H i and Li i . Using the Ca ii K line as a reference element, we infer N ( 7 Be)/ N (H) ≈ 7.4 × 10 −6, or ≈ 9.8 × 10 −6 when the 7 Be decay is taken into account. The 7 Be abundance is about half of the value most frequently measured in novae. The possible presence of overionization in the layers where 7 Be ii is detected is also discussed. Observations taken at the Telescopio Nazionale Galileo in La Palma 91 days after discovery showed prominent emission lines of oxygen and neon, which allow us to classify the nova as ONe type. Therefore, although 7 Be is expected to be higher in CO novae, it is found at comparable levels in both nova types.